2014
DOI: 10.1159/000355781
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Blood Levels Before and After Kidney Transplantation

Abstract: Background/Aims: Sclerostin is secreted by osteocytes. As a circulating inhibitor of the Wnt-signaling pathway it inhibits bone formation and contributes to the development of osteoporosis. Sclerostin levels are elevated in patients with chronic kidney disease and end-stage renal disease. Since data for patients after kidney transplantation are scarce, we have prospectively measured sclerostin levels before and during the first year after renal transplantation and have examined the association of sclerostin wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 34 publications
6
44
3
2
Order By: Relevance
“…At the same time he showed that these markers reflected bone turnover in dialysis patients so that they still had information value in its assessment [28]. Another relatively new marker, sclerostin, studied in progressed CKD or transplanted population [9,29] would be of interest, unfortunately we did not include it into the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time he showed that these markers reflected bone turnover in dialysis patients so that they still had information value in its assessment [28]. Another relatively new marker, sclerostin, studied in progressed CKD or transplanted population [9,29] would be of interest, unfortunately we did not include it into the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…As far as sclerostin is concerned, recent clinical data argue against simple renal retention, since in parallel with increasing serum concentrations, urinary sclerostin concentrations as well as fractional sclerostin excretion also increase with declining renal function (the latter from 0.45±0.26 % in patients with CKD stage 1 to 26±18 % (n=15) in CKD stage 5 (n=19) [47]. Serum levels rapidly return to the normal range following successful renal transplantation [48]. If elevated sclerostin levels are not solely consequential to renal retention, increased production comes into play.…”
mentioning
confidence: 99%
“…Also the study by Bonani et al showed a dramatic sclerostin decrease after kidney transplantation in patients with ESRD. This effect can predominantly be explained by the improved kidney function [23].…”
Section: Discussionmentioning
confidence: 99%